(untitled) (World Science, 2016)
In this paper, the research of multi-directional transfer mode. As a result of investigations it was established that it is widely used in the provision or distribution of multimedia services group. This ensured efficient use of frequency resources, which are systems 802.11. This in turn reduces the value of the effective rate, making the channel an additional service information.